The effect of course design on surrogate measures of injury risk in women and men world cup skicross - Tomelleri, L.; Mannsåker, I. H.; Lachaize, T.; Wortelboer, W.; Lasshofer, M.; Gilgien, M. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: In skicross, the number and severity of injuries are among the highest and most serious in winter sports [1]. The specific aspect of skicross is the head-to-head racing during the finals and the course, which is made up of different types of obstacles. Previous research has linked injuries to three types of obstacles (jumps, turns and rollers) and the injuries were primarily caused by unintentional contact between skiers and personal error [2,3]. To provide a more comprehensive picture of the factors that might lead to injuries, this study assumed that surrogate measures of injury risk (hereafter named "events"), such as crashes, are related to actual injury risk. Based on this assumption this study investigated how course characteristics affected these injury risk metrics for women and men.